2020
DOI: 10.1080/0144929x.2020.1772879
|View full text |Cite
|
Sign up to set email alerts
|

Inattentive, imprudent and inapt: discovering inadequacies of ICT during life-changing events through the lens of non-users

Abstract: Life-changing events (or LCEs) can alter a person's status quo and threaten well-being. Previous research investigated distinct LCEs, where participants already used technology routinely. This paper reports the results of two field studies through which we compared supports people refer to when experiencing different LCEs. Together with users of technology, our sampling included participants who specifically did not refer to online services and tools to seek help during their LCE. We found that popular service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…Although social media can be beneficial during life changes and more broadly, people also face challenges using social media and social technologies during transitional life periods (Cherubini, Reut, Tyler, & Ortlieb, 2020). Challenges are sometimes due to norms and expectations within people's networks or on social media sites, which may constrain self‐disclosures (Andalibi & Forte, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Although social media can be beneficial during life changes and more broadly, people also face challenges using social media and social technologies during transitional life periods (Cherubini, Reut, Tyler, & Ortlieb, 2020). Challenges are sometimes due to norms and expectations within people's networks or on social media sites, which may constrain self‐disclosures (Andalibi & Forte, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Figueiredo et al [11] found that women use fertility apps in a holistic way, to follow multiple goals as they go through life transitions. Cherubini et al [3] highlight the importance of online communities for helping women find and share information about their pregnancies. Similarly, Massimi et al [19] showed how women use online pregnancy communities for emotional support, friendship and informational support in various decisions such as a home birth or going to hospital as they transition into pregnancy.…”
Section: Related Workmentioning
confidence: 99%